Advantages of Minimal Access Versus Conventional Aortic Valve Replacement in Elderly or Severely Obese Patients. Issue 2 (March 2017) - Pisano, Calogera; Totaro, Pasquale; Triolo, Oreste Fabio; Argano, Vincenzo
Abstract : Objective: The aim of our study was to investigate potential clinical advantages of minimal access versus conventional surgical approach in older and severely obese patients undergoing isolated aortic valve replacement (AVR). Methods: One hundred thirty-five patients undergoing isolated primary AVR were enrolled. Propensity score matching was used to compare 42 selected patients operated on ministernotomy (MS, group B) with 42 selected patients operated on full sternotomy (FS, group A). Results: After propensity score matching, the two groups were comparable in terms of preoperative characteristics. Cardiopulmonary bypass time was significantly longer in MS group compared with the FS group [median (95% confidence level or CL), 103 (98.7–106.4) vs 94 (83.6–99) minutes, respectively; P = 0.0019]. No significant difference was observed in aortic cross-clamp time [median (95% CL), 73 (71.1–78.2) vs 69.5 (62.7–83) minutes; P = 0.4]. Significantly shorter ventilation time [median (95% CL), 13 (12–16.4) vs 24 (22–25) hours; P = 0.00018], intensive care unit stay [median (95% CL), 1 vs 2 days; P = 0.00017], and hospital stay [median (95% CL), 8.5 (8–10.8) vs 13.5 (11.1–14) days; P = 0.00030] were shown in the MS group. The age subgroup analysis showed that statistical significance for mechanical ventilation, intensive care unit, and hospital stay was specific for patients older than 75 years. The analysis of body mass index quartile showed that statistical significance for mechanical ventilation was specific for patients in the fourth quartile. Conclusions: Minimal access AVR is a reproducible, safe, and effective surgical option in patients candidate for isolated AVR, and our study suggests a faster recovery when used in severely obese or older patients.